Hasil Belajar Peserta Didik Kelas V Sekolah Dasar Menggunakan Teka-teki Silang - nur aniza (Universitas Sriwijaya, 2019)
Abstract: This study was aim to describe the improvement of the learning outcomes of Grade V students of SD Negeri 91 Palembang in subtheme of The Nationality Events of Colonial Period using by Crossword Puzzle learning strategy. This study method was Classroom Action Research. Classroom Action Research consists of four stages, that is planning, implementation, observation, and reflection. The results showed that the value of learning outcomes and the activity of students were increased. It can be seen from the learning completeness of students in Cycle I with an average of 73,1 and percentage of 61,5%. In Cycle II, the average learning completeness of students increased to 83,3 with a percentage of 84,6%. From the results of observation, the value of students activeness in cycle I reached an average of 63,3 and a percentage of 63,3% with the active category. In cycle II, the average activity of students increased to 81,7 and a percentage of 81,7% with a very active category. Based on the results of these studies it can be concluded that learning by using Crossword Puzzle Learning Strategy can improve student learning outcomes in the subtheme of The Nationality Events of Colonial Period in grade V of SD Negeri 91 Palembang.Keywords: Learning outcomes, Crossword Puzzle learning strategy Abstrak: Penelitian ini bertujuan untuk mendeskripsikan peningkatan hasil belajar peserta didik kelas V SD Negeri 91 Palembang pada subtema Peristiwa Kebangsaan Masa Penjajahan menggunakan strategi pembelajaran Teka-teki Silang. Metode penelitian ini adalah Penelitian Tindakan Kelas. Penelitian Tindakan Kelas terdiri dari empat tahapan, yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Hasil penelitian menunjukkan bahwa nilai hasil belajar dan keaktifan peserta didik mengalami peningkatan. Hal ini dapat dilihat dari ketuntasan belajar peserta didik pada siklus I dengan rata-rata 73,1 dan persentase sebesar 61,5%. Pada siklus II, rata-rata ketuntasan belajar peserta didik meningkat menjadi 83,3 dengan persentase sebesar 84,6%. Dari hasil observasi, nilai keaktifan peserta didik pada siklus I mencapai rata-rata 63,3 dan persentase sebesar 63,3% dengan kategori aktif. Pada siklus II, rata-rata keaktifan peserta didik meningkat menjadi 81,7 dan persentase sebesar 81,7% dengan kategori sangat aktif. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa pembelajaran dengan menggunakan strategi pembelajaran Teka-teki Silang dapat meningkatkan hasil belajar peserta didik pada subtema Peristiwa Kebangsaan Masa Penjajahan di kelas V SD Negeri 91 Palembang.Kata kunci:Hasil belajar, strategi pembelajaran Teka-teki Silang